A new species of Meligethes (Coleoptera: Nitidulidae: Meligethinae) of the M. lugubris complex from Sardinia - Audisio, Paolo; de Biase, Alessio; Trizzino, Marco; Mancini, Emiliano; Antonini, Gloria (Zootaxa, 2009)
A combined morphological and bionomical analysis was performed to clarify the position of a problematic species of the Meligethes lugubris group from Sardinia and Corsica (Coleoptera, Nitidulidae, Meligethinae). This species-group is represented by a dozen anthophagous species associated with Lamiaceae, and distributed from North Africa to Japan. The analysis was mainly focused on the specific distinction and formal description of a new species, M. foddaii Audisio, De Biase & Trizzino sp. nov., from Sardinia and Corsica. The species is morphologically scarcely distinguishable from the allopatric M. lugubris Sturm and M. gagathinus Erichson (both widespread in southern Europe). An identification key to Euro-Mediterranean members of the M. lugubris complex is provided. Combined morphological, ecological, phenological, and preliminary molecular data are presented to support the distinction of the new species. The palaeogeographical scenario explaining the likely Plio-Pleistocene differentiation of the three species, which are all associated with the related Lamiaceae genera Mentha and Thymus, is also briefly discussed.